Terminação de bovinos aos 18 meses com diferentes condições sexuais suplementados em pastagem de aruana - Teixeira, Odilene de Souza (2016)
This study aimed to evaluate performance, behavior as well as meat and carcass characteristics of beef cattle with different sexual conditions, finished at 18 months, raised on Aruana (Panicum maximum Jacq cv. Aruana) pasture, receiving energy supplementation. The treatments consisted of surgically castrated, immunocastrated or non-castrated animals. The experiment consisted of 39 contemporary male bovine animals with initial body weight of 284.1 ± 31.4 kg and average age of 14 months. Chemical composition analysis and patterns of pasture production did not differ among treatments. Average daily gain, final weight and live weight gain per hectare, were not influenced by the sexual condition. In assessing the agonistic behavior of the animals, non-castrated animals more often displayed aggressive activities such as threats and fights when compared to immunocastrated animals. Feeding behavior, grazing time, rumination and idleness were not affected by treatments. Non-castrated animals spent more time at the feeder (56.20 minutes) than either surgically castrated (41.43 minutes) or immunocastrated, (32.38 minutes).. As for carcass attributes, no difference was found for slaughter weight, hot and cold carcass weight and their respective yields. Regarding Muscle and fat yield per 100 kg of cold casting, non-castrated animals had higher muscle ratio (67.9%) vs. castrated calves (65.1%) or immunocastrated (64,1%) in detriment of the greater proportion of fat found in castrated animals. Regarding meat characteristics, meat from immunocastrated and surgically castrated animals demonstrated color with greater intensity of red and yellow hues. The characteristics evaluated by the taste panel did not differ for any of the evaluated sexual conditions and were classified as "slightly above average". The combination of the correct handling of Aruana grazing and the use of supplementation was promising for finishing cattle with different sexual conditions at 18 months of age, considering that there was no difference in average daily gain, final weight and gain liveweight per hectare. Castrates both surgically as immunocastrated obtained higher yield of fat in the carcass while uncastrated animals have higher muscle performance. In the flesh, there was difference in the color, and steers (surgically or immunocastrated) produced meat prone to lighter red color compared to uncastrated cattle. In choosing the method recommended castration this latter, to be a less invasive method for cattle, which determines greater preservation of animal welfare.